2014
DOI: 10.11604/pamj.2014.19.172.4718
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices of HIV post exposure prophylaxis amongst health workers in Lagos University Teaching Hospital

Abstract: IntroductionTimely PEP after needle stick exposure to high risk body fluids can reduce the rate of occupational transmission significantly. Ignorance of this may increase the risk of seroconversion to HIV for healthcare workers. This study was conducted with the aim of demonstrating the current level of knowledge and practise of healthcare workers as regards PEP.MethodsThis was a cross-sectional study, pretested questionnaire were self administered to 372 health workers from various clinical specialties. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
38
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 12 publications
10
38
2
Order By: Relevance
“…The proportion of respondents that knew the recommended PEP drug regimen in this study (30.2%) corroborates with the study done in Cameroun [8]. The high proportion of respondents that knew the correct duration of treatment is similar to that reported in the study conducted in Lagos [17] and Abuja [18]. However, the level of good knowledge reported in this study (39.7%) is less than that reported in a study conducted in North West Ethiopia [15].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The proportion of respondents that knew the recommended PEP drug regimen in this study (30.2%) corroborates with the study done in Cameroun [8]. The high proportion of respondents that knew the correct duration of treatment is similar to that reported in the study conducted in Lagos [17] and Abuja [18]. However, the level of good knowledge reported in this study (39.7%) is less than that reported in a study conducted in North West Ethiopia [15].…”
Section: Discussionsupporting
confidence: 88%
“…Another study conducted in Dares Salaam, Tanzania, revealed a higher prevalence of possible occupational exposure to HIV, but a similar level of utilization following the exposure [21]. The level of PEP utilization as reported in this study is higher than that reported in a study conducted at Lagos, Nigeria [17]. In comparison with a descriptive cross-sectional study conducted at Enugu State [13], this study recorded very similar level of HIV PEP utilization.…”
Section: Discussionsupporting
confidence: 57%
“…Forty‐seven questions in nine papers were on antiretroviral medications for HIV/AIDS . In these papers, it is reported that HCPs lacked knowledge on use of microbicides to prevent HIV and other sexually transmitted diseases, that they were unable to identify medications used for post‐exposure prophylaxis (PEP), and did not know the time point to initiate PEP, duration of treatment and effectiveness of PEP.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-seven questions in nine papers were on antiretroviral medications for HIV/AIDS [30][31][32][33][34][35][36][37][38]. In these papers, it is reported that HCPs lacked knowledge on use of microbicides Tool (questionnaires) validation: a Self-made with expanded/formal validation process, b Self-made with pretest only, c Cited previous developed tool and used as such, or d Cited previously developed tool with modification, and e Self-made without clear explanation for validation…”
Section: Disease Focusmentioning
confidence: 99%
“…Ninety percent of these exposures occur in developing countries thereby increasing HCWs' proneness to HIV infection in these countries. 6 , 7 Despite underreporting, occupational exposures are estimated to be responsible for nearly 1,000 HIV infections each year. 6 -8 The introduction of antiretroviral therapy (ART) has improved the outcomes for infected individuals, and pre-and post-exposure prophylaxis have considerably reduced infections in some exposed individuals.…”
Section: Implications For the Publicmentioning
confidence: 99%